Use of Digital Technologies for the Conduct of Work in the Government System Based on the Demans of the Current Times - ugli, Tanirbergenov Sultanbek Sadik (Indonesian Journal Publisher, 2024)
This article deals with the issues of ensuring the safety of the population in the residences of citizens. It is planned to implement an electronic platform that allows for quick collection and analysis of information on the technical and social condition of residential areas. These strategies focus on digital transformation in the national economy, industry, and society. In Uzbekistan, significant steps have been taken to implement modern information and communication technologies (ICT) in public administration, education, healthcare, and agriculture. One notable challenge addressed in this study is the management of carbon monoxide poisoning, fire hazards, and explosions during the heating season. The research highlights the limitations of manual data collection, including the risk of data loss, difficulty in locating information, and inefficiencies in processing critical safety data. The program processes data in less than a minute, facilitating more efficient emergency management and preventive measures. This system exemplifies the role of digital technology in enhancing public safety and optimizing government operations.